A Fused Maxillary Central Incisor and Its Multidisciplinary Treatment: An 18-Year Follow-Up - Lluís Brunet-Llobet; Jaume Miranda-Rius; Eduard Lahor-Soler; Abel Cahuana (Case Reports in Dentistry)
Fused teeth may cause aesthetic, spacing, periodontal, eruption, and caries problems. The present case report describes a 7-year-old boy patient with a chief complaint of unerupted maxillary incisor. Radiographic examination indicated a fused tooth which had two fused roots but two independent root canals. A complex management of a fused tooth is really difficult to standardize. In this case an orthodontic, endodontic, and surgical treatment (intentional replantation) allowed the tooth to be retained until 18 years following intervention. Maintenance of the root and alveolar bone in young adults at least until full skeletal maturation should be the main treatment objective.